Naprava s pnevmatično aktivno površino: Tehnike krmiljenja lege togih objektov s povratno zvezo in brez nje - Uran, Suzana (Strojniški vestnik, 2002)
The current lack of manufacturing techniques for handling very high volumes of small objects presents a technology barrier to commercial success in various fields like micro-electromechanical systems (MEMS). A fundamentally new approach to automated, massive, parallel manipulation of small-sized parts is explored in this paper: the pneumatic active surface device (PASD). With the appropriate choice of force - caused by blowing or sucking air-flow through the tubes of the pneumatic active surface device - objects placed on the array can be moved in useful ways. Such a device offers great flexibility and speed and can be employed to position, orient, identify sort, feed and assemble parts or objects. Another advantage is that several objects can be controlled simultaneously. This paper describes experimental work on a prototype pneumatic active surface device, in particular an open-loop and closed-loop positioning control techniques for sub-millimeter rigid objects.
Keywords: deli mali; manipulacija predmetov; naprave pnevmatične; zaznavanje predmetov; regulacija lege; strojni elementi; majhni predmeti; avtomatizacija; manipulacija; pnevmatske naprave